2021
DOI: 10.14309/ajg.0000000000001191
|View full text |Cite
|
Sign up to set email alerts
|

Do Children With Functional Abdominal Pain Benefit More From a Pain-Specific Cognitive-Behavioral Intervention Than From an Unspecific Attention Control Intervention? Results of a Randomized Controlled Trial

Abstract: INTRODUCTION: We aimed to compare the efficacy of cognitive-behavioral therapy (CBT) among children with functional abdominal pain with an attention control (AC), hypothesizing the superiority of CBT group intervention regarding pain intensity (primary outcome), pain duration and frequency (further primary outcomes), functional disability, and quality of life and coping strategies (key secondary outcomes). METHODS: We conducted a prospective, multicente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…Sixty-seven records of 33 RCTs were included in the review. The included studies had a total sample of 2622 children with an age range of 4 to 18 years (median [range] age, 12 [7-17] years; 838 boys [32.7%]; 1726 girls [67.3%]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sixty-seven records of 33 RCTs were included in the review. The included studies had a total sample of 2622 children with an age range of 4 to 18 years (median [range] age, 12 [7-17] years; 838 boys [32.7%]; 1726 girls [67.3%]).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies compared CBT with no intervention, 5 studies compared CBT with educational support, 3 studies compared yoga with no intervention, 2 studies compared hypnotherapy with no intervention, 2 studies compared gut-directed hypnotherapy with hypnotherapy, and 2 studies compared guided imagery with relaxation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent 2 years, a large number of clinical studies had taken CBT as a management measure of different kinds of pain, including mixed unlocated chronic pain [ 7 18 ], back pain [ 19 , 20 ], low back pain [ 21 – 26 ], chronic pancreatitis [ 27 ], fibromyalgia [ 28 , 29 ], functional abdominal pain [ 30 ], trigeminal neuralgia [ 31 ], haemophilia pain [ 32 ], osteoarthritis pain [ 33 35 ], perioperative pain [ 36 – 39 ], orofacial pain [ 40 ], diabetic peripheral neuropathic pain [ 41 ], and provoked vestibulodynia [ 42 ]. Previous studies on structural changes in the brain of patients with chronic pain indicated the presence of neuroplasticity in areas associated with the experience and anticipation of pain [ 43 ].…”
Section: Structural and Functional Changes Of The Brain Due To Cbtmentioning
confidence: 99%